Records of the Colony of Rhode Island and Providence Plantations, in New England 567 (vol. 7, 1862) - (:unkn) unknown (General Publisher, 1776)
Required any male citizen age sixteen or above to take a loyalty oath and failure to do so without providing porper justificaito results in disarmament
--
Keywords: POSSESSION - DANGEROUS PERSONS